COMPARATIVE LINGUISTICS AND ITS HISTORY (ResearchJet Journal of Analysis and Inventions, 2021)
The article discusses the problem of terminological differentiation of two disciplines as part of comparative linguistics, studying related languages in diachronic (compare historical linguistics) and in synchrony; for terminological marking of the second In this direction, the term "comparative synchronic linguistics" is introduced.